2020
DOI: 10.3389/fnbeh.2020.00157
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Estrogen Receptor 1 Knockout Deteriorates MK-801-Induced Learning and Memory Impairment in Mice

Abstract: The role of estrogen receptors in neuroprotection and cognition has been extensively studied in humans over the past 20 years. Recently, studies have shifted their focus to the use of selective estrogen receptor modulators in the treatment of mental illnesses in the central nervous system. We conducted this study to test the behavioral changes shown by G protein-coupled estrogen receptor 1 knockout (GPER1 KO) and wild-type (WT) mice with MK-801-induced schizophrenia (SZ). GPER1 KO and WT mice received intraper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, we explored the NMDA-CaMKII signal pathway which is upstream of nNOS. As a downstream signal factor of the NMDAR subunit, CaMKII is an extremely abundant protein kinase in brain tissue that participates in a variety of signaling cascade reactions and is an important mediation center for the regulation of learning and memory ( Zhang C. et al, 2020 ). CaMKII has been shown to reposition within the NMDAR complex in response to non-ionotropic NMDAR signaling ( Aow et al, 2015 ; Stein et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we explored the NMDA-CaMKII signal pathway which is upstream of nNOS. As a downstream signal factor of the NMDAR subunit, CaMKII is an extremely abundant protein kinase in brain tissue that participates in a variety of signaling cascade reactions and is an important mediation center for the regulation of learning and memory ( Zhang C. et al, 2020 ). CaMKII has been shown to reposition within the NMDAR complex in response to non-ionotropic NMDAR signaling ( Aow et al, 2015 ; Stein et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…GPER has been associated with several physiological functions, such as angiogenesis, brain development, and homeostasis [28,101], but it also participates in several pathological processes, such as carcinogenesis and metastasis development [74][75][76]. Although GPER improves the correct development of neuronal, connective, and epithelial tissues [35,36], changes in its expression can deregulate homeostasis and trigger malignant development [31]. GPER expression levels depend on the cancer type, which could serve as a prognosis marker for the tissue affected [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the Gβγ subunit could transactivate the epidermal growth factor receptor (EGFR) via heparin-binding EGF-like growth factor (HB-EGF) activating the phosphatidylinositol 3-kinase (PI3K) and MAPK pathways (Figure 2) [30,31]. Furthermore, these mechanisms have been associated with the proliferation of non-tumorigenic breast cells MCF10A ex vivo [32], dendritic spin density related to spatial learning and memory [33][34][35], and glucose and lipid homeostasis [36].…”
Section: Gper/gpr30 Signaling In Normal Tissuesmentioning
confidence: 99%
“…Therefore, it is reasonable to find increased expression of pro-apoptotic protein marker-Bax, and decreased expression of anti-apoptotic protein-tyrosine hydroxylase in the brains of MK-801-treated mice. The brain regions we tested included prefrontal cortex and hippocampus, which are believed to be important for the onset and/or development of SCZ ( 33 ). In fact, clinical data indicated that the loss of neurons in brains of SCZ patients, especially in the prefrontal cortex, was the basis of many core symptoms of SCZ and was closely related to the prognosis of the disease ( 34 ).…”
Section: Discussionmentioning
confidence: 99%